Perlindungan Hukum terhadap Saksi dan Korban Dalam Undang-Undang LPSK - Putri Ramadhani Rangkuty; Sumantri Ritonga; Muhammad Aldi Khoiri; Mirna Syahfitri Rahmadani; Putri Nabila Sitorus Pane (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The protection of witnesses and victims is a crucial element in the enforcement of criminal law to ensure legal certainty, justice, and the fulfillment of human rights. Law Number 13 of 2006 on the Protection of Witnesses and Victims established the Witness and Victim Protection Agency (LPSK) as an independent institution responsible for providing protection and assistance throughout the criminal justice process. This study aims to analyze the mechanisms and forms of legal protection provided by LPSK to witnesses and victims in criminal proceedings. The research employs a normative juridical method using statutory and conceptual approaches through library research of laws, legal doctrines, and relevant literature. The results indicate that LPSK offers various forms of protection, including physical and psychological protection, legal safeguards, and the fulfillment of procedural rights. However, the implementation of protection has not been fully optimal due to procedural complexities and inter-agency coordination issues. In conclusion, LPSK plays a vital role in supporting justice, yet strengthening regulations and implementation mechanisms is necessary to enhance the effectiveness of witness and victim protection.